2011
DOI: 10.1162/edfp_a_00045
|View full text |Cite
|
Sign up to set email alerts
|

When the Bell Tolls: The Effects of School Starting Times on Academic Achievement

Abstract: A number of high schools across the United States have moved to later bell times on the belief that their previous bell times were too early for the "biological clocks" of adolescents. This paper studies whether doing so improves academic performance. I first focus on the Twin Cities metropolitan area, where Minneapolis and several suburban districts have made large policy changes but St. Paul and other suburban districts have maintained early schedules. I use individual-level ACT test score data on all indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
104
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(107 citation statements)
references
References 27 publications
3
104
0
Order By: Relevance
“…Reference lists of articles identified in Steps A and B and reviews of the topic of school start times were reviewed for identification of additional reports (Step C). Several of the earliest studies with results presented in abstract form only were identified in this manner, as were some studies from the education or economics literature that were not indexed by PubMed . A Scopus search for “school start time” (all fields) found 320 documents (Step D), of which 3 satisfied the inclusion criteria and had not been identified in previous steps.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reference lists of articles identified in Steps A and B and reviews of the topic of school start times were reviewed for identification of additional reports (Step C). Several of the earliest studies with results presented in abstract form only were identified in this manner, as were some studies from the education or economics literature that were not indexed by PubMed . A Scopus search for “school start time” (all fields) found 320 documents (Step D), of which 3 satisfied the inclusion criteria and had not been identified in previous steps.…”
Section: Methodsmentioning
confidence: 99%
“…Five of these reports are listed more than once in the table. Three reports included multiple study populations whose data are analyzed separately . Three reports included cross‐sectional and longitudinal components, with data for each component presented separately …”
Section: Methodsmentioning
confidence: 99%
“…He uses ACT test score data on all individuals from public high schools in the Twin Cities metropolitan area who took the ACT between 1993 and 2002 to estimate the effects of school starting times on ACT scores. Hinrichs (2011) broadens his analysis by estimating the effects of start time on achievement using statewide standardized test scores from Kansas and Virginia. His results suggest no effect of school start time on academic achievement.…”
Section: B the Link Between Sleep And Academic Achievementmentioning
confidence: 99%
“…Indeed, numerous cross-sectional and observational studies have suggested the benefit of delayed school start times. These studies usually compared one school district or class with another that used a later start time and revealed that adolescents in schools with later start times have less daytime sleepiness and sleep restriction,[8, 32–35] improved sleep quality,[36] better behavior, attention and concentration in class,[34, 35] less tardiness,[37] higher academic achievement in some[35, 38] but not all schools,[39] and fewer motor vehicle accidents. [21] The effects of later school start times compared favorably with other educational interventions in terms of overall cost and commensurate academic success.…”
Section: Introductionmentioning
confidence: 99%